Particulate matter-induced epigenetic modifications and lung complications - Muhammed Afthab; Shadi Hambo; Hyunji Kim; Ali Alhamad; Hani Harb (European Respiratory Review)
Air pollution is one of the leading causes of early deaths worldwide, with particulate matter (PM) as an emerging factor contributing to this trend. PM is classified based on its physical size, which ranges from PM10 (diameter ≤10 μm) to PM2.5 (≤2.5 μm) and PM0.5 (≤0.5 μm). Smaller-sized PM can move freely through the air and readily infiltrate deep into the lungs, intensifying existing health issues and exacerbating complications. Lung complications are the most common issues arising from PM exposure due to the primary site of deposition in the respiratory system. Conditions such as asthma, COPD, idiopathic pulmonary fibrosis, lung cancer and various lung infections are all susceptible to worsening due to PM exposure. PM can epigenetically modify specific target sites, further complicating its impact on these conditions. Understanding these epigenetic mechanisms holds promise for addressing these complications in cases of PM exposure. This involves studying the effect of PM on different gene expressions and regulation through epigenetic modifications, including DNA methylation, histone modifications and microRNAs. Targeting and manipulating these epigenetic modifications and their mechanisms could be promising strategies for future treatments of lung complications. This review mainly focuses on different epigenetic modifications due to PM2.5 exposure in the various lung complications mentioned above.